Kajian Komoditas Ekspor Unggulan pada Sektor Industri Pengolahan Jawa Timur dalam Menghadapi RCEP - Jodi Rizki Kusuma; Achmad Room Fitrianto (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This research aims to analyze the best leading commodities from the processing industry sector to face the Regional Comprehensive Economic Partnership (RCEP) trade agreement. The 15 leading commodities come from each sub-sector of the processing industry which is the leading variable in RCEP member trading, making it a testing variable. Variable samples are from 2015-2020. Variable analysis using data from BPS East Java, and tested using Two Way ANOVA test. The results showed a significant difference from the export index of each leading commodity as a whole as well as specific, while showing the best leading commodities in terms of international market demand RCEP countries. Research shows that the highest advantage is found in the commodity sub-sector of mineral processing (2.74), while the lowest advantage in commodities sub-sector of the textile processing industry (0.09).